Nutritional Status and Its Determinants Among Children Under Five in Remote Areas - Suardika, I Nyoman Watra; Bolkiah, Hafizah Hayatul (Lembaga Publikasi Ilmiah Nusantara, 2025)
Malnutrition among children under five remains a significant public health concern, particularly in remote areas with limited access to healthcare, education, and nutritious food. This study aims to assess the nutritional status of children under five and identify its key determinants in remote communities. A cross-sectional survey was conducted involving 250 children aged 6–59 months in selected remote villages. Nutritional status was assessed using anthropometric indicators such as weight-for-age, height-for-age, and weight-for-height, following WHO standards. Socio-demographic and environmental data were collected through structured interviews with caregivers. The results showed that 34.8% of children were stunted, 21.2% were underweight, and 11.6% were wasted. Multivariate logistic regression analysis revealed that low maternal education, inadequate dietary diversity, poor sanitation, and limited access to health services were significantly associated with malnutrition. These findings highlight the urgent need for targeted nutrition interventions and integrated development strategies to address the underlying factors contributing to poor nutritional outcomes in remote settings.